ANALISIS KUAT TEKAN REACTIVE POWDER CONCRETE DENGAN VARIASI SILICA FUME DAN LIMBAH SERBUK MARMER PADA PERAWATAN STEAM CURING - Arumningsih , Dian; Sumina, Sumina; Priyanto, Kusdiman Joko; Putri, Dinda Ajeng Anindita (Journal of Civil Engineering and Infrastructure Technology, 2025)
In the current era of globalization, the need for concrete is increasing, triggering challenges to create good quality concrete. High- quality concrete innovation is developed through the improvement of concrete constituent materials and the addition of added materials. In this study, pozzolan material was used, namely silica fume and marble powder as filler. This concrete is Reactive Powder Concrete, where the constituent material of concrete is nanometer in size and removes coarse aggregate. The method used is experimental. The test specimen used is cylindrical concrete measuring 10 cm x 20 cm. This study aims to determine the optimum level of use of silica fume and marble powder with a variation in 0% levels; 5%; 10%; 15%; 20%; 25%; 30%; 35%; 40%; 45%; and 50%. The results of the study showed the optimum content of silica fume 15% of the total cementitious, and the optimum content of marble powder 30% of the total fine aggregate which obtained compressive strength of 12.74 MPa and 12.10 MPa at the age of 7 days. Then 16 pieces of RPC concrete were made with a test life of 7, 14, 21, and 28 days. Test specimens are given two treatment methods, namely steam curing and immersion. Of the two treatments applied, steam curing produces high initial compressive strength, with a maximum compressive strength of 66.24 MPa at 7 days old. While immersion treatment can produce high final compressive strength in RPC concrete which produces the highest compressive strength of 103.82 MPa at 28 days old.